The Effectiveness of Augmented Reality in Improving Students Motivation: An Experimental Study - Malek Jdaitawi; Fatima Muhaidat; Ayat Alsharoa; Abeer Alshlowi; Marwa Torki; Mona Abdelmoneim (Athens Institute for Education and Research, 2023)
Augmented reality (AR) has become a potential technology tool to improve the skills of students with learning disabilities. The effects of AR technology approach on students with learning disabilities motivation levels is considered as the research motivation. This study examined the effect of the AR on Jordanian 6th grade students' motivation levels. A quantitative quasi-experimental study is preceded with the pretest-posttest control group design model, where 24 students who identified to have learning disabilities were participated in this study and were randomly divided into two groups. Two groups, control group 12 students were taught conventionally, and 12 students were designated as the experimental group, they used the AR technology for four weeks. The results show significant results for the AR technology in enhancing student motivation. The results concluded the effectiveness of AR technology in enhancing students' motivation.